(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The article deals with the enrichment of sour-milk drinks with natural fruit fillers. The effects of quality nutrition on human physiology andmental abilities are investigated. The indispensability of natural foods for human health and vitality is noted.